Analysis Identification of Composition Catches Bubu Naga Operated in Cangkring Pond Waters, Indramayu Regency, West Java - Abdul Hadi; Didha Andini Putri; Lukman Fitrahsaeri (Barakuda'45, 2022)
The residents of Cangkring Village, Centigi District, mostly work as fishermen. One type of fishing gear used for catching is the dragon trap, with the main target catch being shrimp. This study aimed to determine the composition of the main catch and by-products of dragon traps and determine the effectiveness of the environmental friendliness of using dragon traps operated in Cangkring waters, Cantigi sub-district, Indramayu Regency. The method used in this research is a descriptive method using primary data and secondary data. The composition of the catches obtained during the study was Penaeus merguensis, Metapenaeus monoceros, Scylla spp, and others such as milkfish, eel, and mullet. The total catch during the study was 39.9 kg. The biggest catch was Penaeus merguensis, as much as 22.1 kg. The main catch during the research was Penaeus merguensis, and the by-catch was: Metapenaeus monoceros, Scylla spp, and others. The resulting catch data is 55% main catch and 45% by-catch. A comparison of HTSU with HTS shows that using dragon traps still needs to be environmentally friendly. However, from the aspect of the utilization of the catch, only a small amount is not utilized (discard catch), namely 2.5%.